A bacterial protein requirement for the bacteriophage lambda terminase reaction. - Gold, M (1986)
The bacteriophage lambda terminase enzyme cleaves the cohesive-end sites of lambda DNA to yield the protruding 5'-termini of the mature molecule. In vitro, this endonucleolytic event requires a protein factor which has been isolated and purified from extracts of uninfected E. coli. The terminase host factor (THF) is a heat stable basic protein of M.W. approximately 22,000. The integration host factor (IHF) protein of E. coli can efficiently substitute for THF in the terminase reaction; however, THF can be demonstrated to be physically present in, and isolated with full biological activity from extracts of cells defective or deficient in IHF.